Monsoon weather and food security in Pakistan - Risto Conte Keivabu; Rumi Chunara (Food Security, 2026)
The intensification of monsoon weather anomalies due to climate change poses significant challenges to food security in South East Asia. In this paper we focus on Pakistan, to understand how dry conditions during the monsoon season affect food security. Using the Standardized Precipitation Evapotranspiration Index, we examine the effects of drier monsoon seasons on self-assessed food security. For this purpose, we leverage Pakistan Social and Living Standards Measurement Survey data for 2019–2020 on 147,063 households and combine it at the district level with the European Re-Analysis-Land meteorological data provided by the Copernicus Data Store. Our findings highlight an 8.5% increase in mild to severe food insecurity with exposure to a dry monsoon season. The impact is mostly concentrated on the quality and diversity of food available suggestive of a change in the food balance rather than in the total caloric intake. We also observe dry conditions to determine a larger decrease in food diversity in individuals with none or low educational attainment. Findings suggest that the increased unpredictability of monsoon weather could exacerbate food insecurity with vulnerable groups being affected foremost in Pakistan and highlights the critical need for measures to mitigate the impact of droughts on food diversity and quality.~
Keywords: 630; Droughts; Food security; Monsoon weather; Pakistan